Endohelminths from five rare species of turtles (Bataguridae) from southeast Asia confiscated by international authorities in Hong Kong, People s Republic of China - Murray, Rebecca A.; Dronen, Norman O.; Blend, Charles K. (Zootaxa, 2004)
Specimens of 5 species of threatened, vulnerable, and endangered turtles (Cuora amboinensis, Cyclemys dentata, Heosemys grandis, Orlitia borneensis, and Pyxidea mouhotii) belonging to Bataguridae, were confiscated in Hong Kong, China on 11 December 2001 by international authorities. A review of the endohelminths previously reported from these turtles was compiled and is summarized herein. Endohelminth studies on these turtle species are reasonably scarce, and this study provided a rare opportunity to examine a limited number of specimens for endohelminths. Seven different parasite species were collected and there were 8 new host records. This is the first record of a parasite from P. mouhotii. This study is intended to provide additional information for comparisons to future parasite studies of species of Asian freshwater turtles.